Analysis of prescriptions for completeness in a tertiary care teaching hospital - Srinivasa, Jyothsnya; Swamy, Shubhatara (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Prescribing errors are major problems among medication errors. Prescribing errors include mistakes or inaccuracies when choosing and ordering treatments, such as wrong doses or illegible prescriptions. Most of these errors result in no harm or have low to moderate harm however, some result in severe harm or death. There are economic consequences attributed to prescribing errors. Methods: The aim of the study was to analyse the prescriptions for completeness. The prospective observational study was conducted in outpatient department of different specialities in a tertiary care teaching hospital. Prescriptions with atleast one antibiotic, was collected through duplicate copies from the prescribing doctors. The data obtained from prescriptions were analysed and the conclusions were drawn using descriptive analysis. Results: A total of 1516 prescriptions with 3957 drugs were prescribed, out of which 1697 were antibiotics. Average number of drugs per prescription was 2.6 and average number of antibiotics per prescription was 1.1. Patient’s name, age, and gender were mentioned in 99%, 87.8%, and 96% of prescriptions respectively. Generic drug names were used in 0.7% of prescriptions. Out of 1681 antibiotics prescribed in 1574 had appropriate dosage form. Conclusions: The present study highlights the problem of incomplete prescriptions and extensive use of brand names. Intervention strategies focused on education and training, introduction of strict feedback control and monitoring systems are highly effective in reducing prescription errors.